The role of π-bonding on the high temperature structure of the double perovskites Ba2CaUO6 and BaSrCaUO6. Issue 36 (28th September 2015) - Reynolds, Emily; Thorogood, Gordon J.; Avdeev, Maxim; Brand, Helen E. A.; Gu, Qinfen; Kennedy, Brendan J.
<x xml:space="preserve">Abstract</x> High temperature synchrotron X-ray and neutron diffraction powder diffraction studies of the uranium perovskites Ba2CaUO6 and BaSrCaUO6 reveal unusual phase transition behavior associated with the progressive loss of cooperative octahedral tilting.